Should School-Level Results of National Assessments Be Made Public? - Atsuyoshi Morozumi; Ryuichi Tanaka (Institute of Labor Economics (IZA), 2020)
Many countries conduct national standardized assessments of educational performance, the results of which may be published at the school level or at a higher level of aggregation. Publication at the school level potentially improves student achievements by holding schools accountable, whereas such accountability pressure may have distributional consequences and/or compromise outcomes beyond education achievements (labeled as non-cognitive skills). Using a Japanese policy reform that created variation in the disclosure system of national assessment results across municipalities, we show that publishing school-level results increases students' test scores across the entire score distribution, with no evidence of adverse impacts on noncognitive skills.
Keywords: D80; I20; I28; 330; national standardized assessments; information disclosure; school-level results; school accountability; student outcomes